Tactical Combat Casualty Care (TCCC): Historical Evolution, EvidenceBased Development, And Contemporary Applications In Modern Warfare - Nizamuddin Ubaidillah (The ASEAN Journal of Military and Preventive Medicine, 2026)
Background:Armed conflict has historically been a major driver of advances in trauma surgery and emergency medicine. Despite remarkable progress in weapons technology during the twentieth century, prehospital combat casualty care evolved more slowly, resulting in a substantial number of preventable battlefield deaths before casualties reached definitive medical treatment. These challenges prompted the development of Tactical Combat Casualty Care (TCCC), an evidence-based combat trauma system specifically designed to integrate medical priorities with tactical realities. Objective:This review aims to describe the historical evolution of Tactical Combat Casualty Care, summarize the scientific evidence supporting its development, and discuss its implementation and continuing adaptation in contemporary armed conflicts. Methods:A narrative literature review was conducted using landmark publications, military trauma registries, clinical practice guidelines, and peer-reviewed articles indexed in PubMed, Scopus, and military medical literature. Historical developments from World War I through modern conflicts in Iraq, Afghanistan, Ukraine, and the Middle East were critically analyzed to identify major milestones in battlefield trauma care. Results:The historical evolution of combat casualty care demonstrates a progressive transition from conventional battlefield first aid to an integrated evidence-based military trauma system. Landmark studies from Iraq and Afghanistan established that approximately one-quarter of battlefield deaths were potentially survivable, with uncontrolled hemorrhage representing the predominant preventable cause of death. These findings fundamentally reshaped combat casualty management through the introduction of the MARCH algorithm, widespread tourniquet application, hemostatic agents, tranexamic acid, damage control resuscitation, and prolonged casualty care. Contemporary conflicts further highlight the need to integrate force protection, drone awareness, tactical evacuation, and operational security into modern battlefield medicine. Conclusion:Tactical Combat Casualty Care has evolved from a protocol developed for United States Special Operations Forces into the international standard for battlefield trauma care. Continuous refinement through military trauma registries, operational experience, and evidence-based research ensures that TCCC remains a dynamic combat casualty care system capable of adapting to the changing nature of modern warfare while substantially reducing preventable battlefield mortality.